Exploring patterns enriched in a dataset with contrastive principal component analysis - Abubakar Abid (Nature Portfolio, 2018)
Dimensionality reduction and visualization methods lack a principled way of comparing multiple datasets. Here, Abid et al. introduce contrastive PCA, which identifies low-dimensional structures enriched in one dataset compared to another and enables visualization of dataset-specific patterns.